Adaptation of international evidence based clinical practice guidelines: The ADAPTE process - Abdelhamid Attia (Middle East Fertility Society Journal, 2013)
Evidence-based clinical practice guidelines are important tools to unify practice and improve patient’s outcomes in terms of morbidity and mortality. The generation of EBCPGs is not an easy task. It requires a lot of resources, expertise and time. So, in low resources countries, adaptation of high quality guidelines is the way to go. This can be done in a scientific way using the ADAPTE methodology and toolkits.